2020
DOI: 10.1177/0081246320954317
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the National Health Insurance Bill for mental health needs: response from the Psychological Society of South Africa

Abstract: This article summarizes the findings of a consultation process initiated at the 25th congress of the Psychological Society of South Africa in September 2019 to submit a response to the national public participation process on the National Health Insurance Bill, 2019. While the Psychological Society of South Africa supports the overall purpose of the Bill, to provide universal health coverage in South Africa, this article critically discusses eight core concerns related to the Bill, including the need to: (1) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…There are growing calls for the integration of mental health services into other primary health care (PHC) [ 10 12 ] including the TB programme. Particularly, evidence of increased comorbidity between mental health disorders and TB [ 13 , 14 ], with mental health rates of up to 84% reported among TB patients [ 13 ], has accentuated the necessity for integrated services.…”
Section: Introductionmentioning
confidence: 99%
“…There are growing calls for the integration of mental health services into other primary health care (PHC) [ 10 12 ] including the TB programme. Particularly, evidence of increased comorbidity between mental health disorders and TB [ 13 , 14 ], with mental health rates of up to 84% reported among TB patients [ 13 ], has accentuated the necessity for integrated services.…”
Section: Introductionmentioning
confidence: 99%
“…The third sub-theme is the need for prioritised funding for children and adolescent mental health. This recommendation is proffered by the Psychological Society of South Africa in line with the anticipated National Health Insurance in SA [26]. The SA national and provincial health departments allocate extremely low amounts of funding towards mental health compared to general hospitals [30].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the growing burden of mental illness the call for an expansion of mental health services in low-and middle-income countries was prompted by the landmark 2007 Lancet series on global mental health. A study done in South Africa (Kleintjes et al, 2020) identified eight core concerns related to the National Health Insurance Bill, including the need to: (1) integrate mental health more effectively into the National Health Insurance Bill; (2) ensure equitable access to health services for all people; (3) improve human resources for mental health; (4) clarify accreditation standards and contractual conditions for service providers; (5) improve utilization of private practitioners within an integrated health system; (6) include mental health expertise in the advisory structures of the National Health Insurance Bill; (7) set out a robust accountability framework within the National Health Insurance Bill; and (8) include mental health indicators in the National Health Insurance information system.…”
Section: Introductionmentioning
confidence: 99%